ANALISIS KAPASITAS TAMPUNGAN DAN KINERJA WADUK UNTUK MEMENUHI KEBUTUHAN AIR TANAMAN NANAS DI PT. GREAT GIANT PINEAPPLE - Rani Sahfitri; Sugeng Prijono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
The reservoir is one of the water sources that can be used for irrigation activities. PT. Great Giant Pineapple utilizes the reservoir function to provide water for irrigation activities. In an era that is increasingly developing now, many things can support success in the agricultural sector. Cropwat for window 8.0 application and ArcGis is one proof of technological advancements in this era. Â The results of this study were to determine the capacity of a reservoir by using two different methods namely bathymetry and DEM and to find out the performance of the reservoir used for irrigation activities based on pineapple plant water requirements.. This research is located in PT. Great Giant Pineapple, Terbanggi Besar, Lampung, conducted in October until November 2019. Based on the results of research that has been done, it is recommended to use the bathymetry method for reservoirs with water-filled conditions and using the DEM method for water-empty reservoirs and it is known that the performance of a reservoir will be affected by the amount of outflow and inflow that occurs in the reservoir and the large reservoir capacity.